GNSS Spoofing Suppression Based on Multi-Satellite and Multi-Channel Array Processing - Ni, Shaojie; Ren, Binbin; Chen, Feiqiang; Lu, Zukun; Wang, Jie; Ma, Pengcheng; Sun, Yifan (Frontiers in Physics, 2022)
The endless spoofing interference affects the credibility of the navigation system seriously. In order to suppress the forward spoofing which is more threatening to military signals in GNSS, this paper proposes a spoofing suppression algorithm based on angle of arrival estimation and mult-satellite fusion. On the basis of successfully suppressing the spoofing signal, the algorithm improves the estimation accuracy of the angle of arrival of the forwarded spoofing and reduces the attenuation of the carrier to noise ratio of the real satellite signal. Finally, the effectiveness of the algorithm is verified by simulation, which has guiding significance for the anti-spoofing research of GNSS.